The Potential of Water-Based Sports in Cultural Viewing - Herita Warni; Syamsul Arifin; Maruful Kahri; Ramadhan Arifin (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
To some extent, the development of sport is influenced by the process of cultural formation. For this reason, it is necessary to explore the potential of culture-based sports by sports experts by paying attention to cultural aspects that allow their potential to be explored and in the end it is expected to produce reliable athletes. However, until now there is almost no research that specifically explores the potential of this culture-based sport. Therefore, this study aims to map the potential of sports that allow for breeding and coaching. This research was conducted through a qualitative approach, with the Naturalistic Inquiry paradigm. Data was collected through interviews, observations and document studies. Source of data for sports management, athletes and documents. The results showed: that 1). Water sports such as diving, rowing, and diving, especially in pool numbers, have the potential to be developed. 2). To be able to develop water sports properly, it is necessary to breed prospective athletes by taking into account the cultural background. 3) The need for continuous management and coaching. The research data is used as study material for local governments and stakeholders in the field of sports to be able to explore the potential of sports that allow them to achieve achievements both at the national and international levels.